2021
DOI: 10.1016/j.jaci.2020.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional translation of IL33 genetics in asthma

Abstract: Background: Asthma is a complex disease with multiple phenotypes that may differ in disease pathobiology and treatment response. IL33 single nucleotide polymorphisms (SNPs) have been reproducibly associated with asthma. IL33 levels are elevated in sputum and bronchial biopsies of patients with asthma. The functional consequences of IL33 asthma SNPs remain unknown. Objective: This study sought to determine whether IL33 SNPs associate with asthma-related phenotypes and with IL33 expression in lung or bronchial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 54 publications
1
31
1
2
Order By: Relevance
“…For example, the A-allele of rs992969, which is associated with an increased risk of AR in the present study, was also significantly associated with higher IL-33 expression in bronchial epithelial cells (P=1.3x10 -6 ) in a previous study (74). A recent study has indicated that the A-allele of rs992969 was significantly associated with a higher mRNA level of IL-33 in bronchial brushes (P=8.3x10 -12 ) (75). In addition, a functional study has revealed that the G-allele of rs928413 was associated with higher IL-33 promoter activity compared with the A-allele in lung cancer cells, and the G-allele of rs928413 included a binding site for cyclic AMP-responsive element-binding protein 1, which is likely an activator of IL-33 transcription in the presence of this allele (76).…”
Section: Discussionsupporting
confidence: 60%
“…For example, the A-allele of rs992969, which is associated with an increased risk of AR in the present study, was also significantly associated with higher IL-33 expression in bronchial epithelial cells (P=1.3x10 -6 ) in a previous study (74). A recent study has indicated that the A-allele of rs992969 was significantly associated with a higher mRNA level of IL-33 in bronchial brushes (P=8.3x10 -12 ) (75). In addition, a functional study has revealed that the G-allele of rs928413 was associated with higher IL-33 promoter activity compared with the A-allele in lung cancer cells, and the G-allele of rs928413 included a binding site for cyclic AMP-responsive element-binding protein 1, which is likely an activator of IL-33 transcription in the presence of this allele (76).…”
Section: Discussionsupporting
confidence: 60%
“…53Recent GWASs have convincingly identified associations of the genetic variants at the IL33 with adult-onset asthma and nasal polyps 38,39,41,42. Genetic signals at the IL33 predominantly associated with blood eosinophil levels in the general population and with an eosinophilic asthma phenotype and also influenced IL33 levels in the airway epithelium, with the risk allele associating with increased IL33 in vivo 54. An epigenetic analysis of human naïve ILC2s activated with IL-25 and IL-33 in vitro revealed that a number of asthma-associated genetic variants localized to ILC2-specific regulatory elements 55.…”
mentioning
confidence: 99%
“…Recently, the IL-33 pathway has been specifically tied to eosinophilic asthma [144]. Therefore, a key area of interest for clinicians is the possibility of a genetic test to identify severe asthma patients with https://doi.org/10.1183/16000617.0183-2021…”
Section: Comorbiditiesmentioning
confidence: 99%